Impact of Incorporating the Principles of International Education in Social Studies Textbooks in Jordan from the point of view Teachers social Education - Abdelmonem Mahmoud Almalkawi, Maryam (Technium Social Sciences Journal, 2020)
The study aimed to identify the extent to which the principles of international education are included in social studies books in Jordan from the point of view of teachers of social education. The study used the descriptive survey method. Through the construction of a tool (a questionnaire) consisting of (29) paragraphs spread over four areas: (Human Rights, the field of world peace, the field of interdependence, the field of diversity), and the sample of the study consisted of (100) teachers of social studies books. The results showed that the degree of inclusion of international education principles in social studies textbooks in Jordan from the point of view of teachers of social education came high in the tool as a whole, and in all areas except the field of diversity, It also showed that there are statistically significant differences attributed to the gender variable and to the benefit of gender (females) in all fields and in the tool as a whole. The study recommended the need to raise awareness of community members, schools and teachers of social studies about the principles of international education and programs.